Cervical Epidural Ewing's Sarcoma Presenting with Rapid Progression: A Case Report - Ali Börekçi; Pınar Kuru Bektaşoğlu; Jülide Hazneci; Adnan Somay; Erhan Çelikoğlu (Boğaziçi Tıp Dergisi, 2023)
Primary extraskeletal Ewing's sarcoma is a highly malignant and extremely rare tumor araising from the soft tissues. There is a peak incidence in the second decade of life. A 24-year-old female presented with rapid loss of weight within 1 month, palpable mass lesion in cervical region, right upper limb pain, weakness in all extremities especially in the right upper limb, difficulty in walking, and urinary incontinence. In her neurological examination, her right upper extremity was parethic (3/5). Spinal magnetic resonance imaging (MRI) revealed an epidural mass lesion located at C7-T1 vertebral level, with prominent spinal cord compression. In T1- and T2-weighted images, the tumor was isointense and heterogeneous contrast-enhancement was prominent. An emergency surgery was undertaken because of rapid deterioration of neurological status. A gross total excision was achieved. Early post-operative neurological examination was normal. The pathology report was Ewing's sarcoma. In her post-operative 1st month, when planning to start oncological treatment, she was referred with right upper extremity paresis and recurrent lesion located at C6-T2 level with spinal cord compression. Urgent surgical intervention was performed due to rapid neurological deterioration. Gross total excision was achieved. Her recurrent pathology was also consistent with Ewing's sarcoma. Oncological treatment was planned with radiotherapy and chemotherapy (Vincristine, actinomycin D, and cyclophosphamide). A repeat MRI was performed at the completion of her treatment which showed no residual tumor at 6th month after surgery. This case highlights the possibility of rapid progression in extraskeletal Ewing's sarcoma and the importance of early diagnosis and intervention.